Das transdermale Permeationsverhalten von Ölkomponenten bei Wasservögeln zur Abschätzung der Prognose einer Rehabilitation nach Ölverschmutzungen im Hinblick auf die Etablierung einer Triage - Klaus, Antonia Maria (Tierärztliche Hochschule, 2017)
Seabirds are important bioindicators, because they are, representing a whole maritime Ecosystem, for humans the visible victims of oil spills. A scientifically proven research plan would make an objective selection of oiled seabirds possible. This would increase the success of rehabilitation and would deliver those from suffering, who are unpromisingly cases. The transdermal permeation of oil components is still unexplored, although an occurred transdermal permeation, in regard of the high toxicity of oil, has great impact of the survival of oil covered birds. The aim of the present study was to detect, if oil components permeate the skin of seabirds within 24 hours. The saltwaterspecies Common Eider, Common Guillemot and Common Scoter belong to the most oiled species because of their lifestyle habits. Mallards are representing sweet – and saltwater birds and were used for reasons of comparison. In-vitro studies with Franz diffusion cells (FRANZ 1975) were conducted, where the non-feathered skin of the lateral thorax was contaminated for 24 hours with three types of oil: Marine Diesel Oil, Light Crude Oil and Heavy Fuel Oil. The acceptor medium was investigated with gas chromatography and mass spectrometry. The outermost layer of the skin, the stratum corneum, is the most important transdermal barrier. Therefore hematoxylin eosin stained cryostat slices were histologically investigated and a measurement of the thickness of stratum corneum and vital epidermis was possible. The sum of these two layers is the thickness of the whole epidermis. High performance thin-layer chromatography (HPTLC) was used to analyze epidermal lipid compositions, because the barrierfunction of the skin is caused by its lipid containing intercellular substance. The epidermal lipid compositions and the morphological parameters of the skin were investigated, to detect the influence of these skin properties on the transdermal permeation of oil components. The analysis of the permeation studies detected a transdermal permeation of three ...